2018
DOI: 10.1002/ehf2.12352
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in surrogate decision‐maker preferences for life‐sustaining treatments of Japanese patients with heart failure

Abstract: AimsPatients with end‐stage heart failure (HF) often require surrogate decision making for end‐of‐life care owing to a lack of decision‐making capacity. However, the clinical characteristics of surrogate decision making for life‐sustaining treatments in Japan remain to be investigated.Methods and resultsAmong 934 patients admitted to our hospital for HF from January 2004 to December 2015, we retrospectively reviewed the medical records of consecutive 106 patients who died in hospital (mean age 73 ± 13 years; m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 31 publications
0
16
1
Order By: Relevance
“…Both HFpEF and HFrEF patients can have multiple comorbidities that can affect their treatments and their clinical course, 52 although the extent of this between the two patterns of HF is controversial 53 . The older HF patients’ needs are not only just for mortality reducing therapies but also for quality of life enhancement, well-designed end-of-life care and the involvement of their carers in decision making thought-out the disease process 54 …”
Section: The Effects Of Comorbiditiesmentioning
confidence: 99%
“…Both HFpEF and HFrEF patients can have multiple comorbidities that can affect their treatments and their clinical course, 52 although the extent of this between the two patterns of HF is controversial 53 . The older HF patients’ needs are not only just for mortality reducing therapies but also for quality of life enhancement, well-designed end-of-life care and the involvement of their carers in decision making thought-out the disease process 54 …”
Section: The Effects Of Comorbiditiesmentioning
confidence: 99%
“…First, the rate of patients' participation increases as the time of the survey becomes more recent. [10][11][12][13] The rise in the participation rate probably re ects the growing interest in ACP.…”
Section: Discussionmentioning
confidence: 99%
“…in palliative care units). [7][8][9][10][11][12][13] Also, factors that associate with patient involvement in such discussions have yet been clear.…”
Section: Introductionmentioning
confidence: 99%
“…Under traditional Japanese culture, patients’ self-determination is sometimes in subordination to the will of the family; the Act on Organ Transplantation in Japan prohibits using organs of patients whose family members refused to offer, even when the patient themselves have a will to donate and have a donor card. As well, a previous study reported that among 934 patients with end-stage heart failure, only 4.7% of patients participated in end-of-life conversations with attending physicians and declared their preferences; surrogates made medical care decisions in 95.3% of cases [11].…”
Section: Discussionmentioning
confidence: 99%